Spectrum of Polypoidal Lesions of the Female Genital Tract - Anu Gupta; Bharti Thaker; Subhash Bhardwaj (Dr. Annil Mahajan, 2022)
Background: Polypoidal lesions of the female genital tract are clinically significant and show various morphological spectrum ranging from inflammatory to neoplastic and may mimic or harbour malignancy. Aim: To study the spectrum of polypoidal lesions in the whole female genital tract and its correlation with clinicopathological parameters was evaluated. Material & Methods: A retrospective study was conducted over a period of 3 years (2018-2021) for all the polypoidal lesions. The relevant details of the patient regarding age, menopausal status, clinical presentation, size of polyp, its location and final histopathological diagnosis were recorded and analysed. The H&E-stained slides were meticulously re-examined and fresh sections were obtained wherever required. Results: Out of a total of 58 polypoidal lesions, maximum were benign 53 (91.37%) and 5 cases (8.62%) were found to be malignant. Uterine polyps (50%) outnumbered all the other polyps of FGT. The age range was between 5 to 70 years with the youngest girl of 5 years diagnosed as Botyroid Rhabdomyosarcoma of vagina and oldest 70 years diagnosed as Squamous cell carcinoma of cervix, both presenting as polypoidal lesions. Abnormal Uterine Bleeding (AUB) was the most common clinical manifestations.